PENGARUH KEPERCAYAAN DAN RESIKO TERHADAP SIKAP DAN PERILAKU DALAM MENGGUNAKAN APLIKASI MOBILE BERBASIS ANDROID - Widyartono, Agustinus; Tyra, Maria Josephine (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The aim of this research is to test the impact risk and trust variable toward behavior with attitude of android mobile application user as mediating variable. Total sample that used in this research 100 respondent. Base on test, instrument that used in this research are valid and reliable. This research used Component Based SEM (Partial Least Square) as method analysis. The output from this research are: (1) Trust and attitude are mediating variable in relations between risk toward attitude and behavior; (2) Risk as attitude form factor and people attitude to use android mobile applications; (3) Risk had negative relations with trust and attitude, as high risk perceived will reduce trust toward applications and attitude; (4) Trust had positive relations toward attitude and attitude had positive relations toward behavior in used android mobile applications.